Underwater mission : 2 graphic adventures - Whitehill, Simcha (Graphix chapters., 2024)
Featuring two full-color graphic stories, this action-packed volume finds Ash, Goh and their Pokémon pals under the sea on a trial mission for Project Mew, while Team Rocket are yet again plagued by bad luck as they go on a wild chase after Pelipper.